Prevalence of Pacifier Sucking Habit and Its Effect on Occlusion in Children Aged 1-5 Years in Baghdad City - Al-Assadi, Aseel H; Al-Dahan, Zainab A (Journal of Baghdad College of Dentistry, 2015)
Background: Non-nutritive sucking habits are common in infants and toddlers. One of the most common non-nutritive sucking habits is pacifier; its prevalence varies from one population to another. This study was conducted to determine the prevalence of pacifier sucking habit among children aged 1-5 years old in Baghdad city and to assess its effect on the occlusion of primary dentition concerning posterior crossbite.Materials and methods: The study was carried out among 1222 children aged 1-5 years old, from which 50 children with continues pacifier sucking habit were chosen to be the study group, compared to 50 children without any sucking habit (control group) matching the study group in age and gender. Children were examined clinically to record the presence of posterior crossbite. Results: The prevalence of pacifier sucking habit was 24.54%; it is tend to decrease with age. Posterior crossbite was found in18% of the pacifier sucking group and all of these cases were unilateral, however, none of the control group had posterior crossbite. In this study girls had higher tendency to suck pacifier and to have posterior ccrossbite than boys. Conclusions: Prevalence of pacifier sucking habit was more among girls, it can cause posterior crossbite which is mainly unilateral and more among girls than boys.